Pendampingan Pembuatan Media Pembelajaran Berbasis Multimedia Powtoon Untuk Meningkatkan Kreativitas Guru MI Miftahul Ulum Sidowungu Kecamatan Menganti - Gresik - Fithriyah, Ainul (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
The use of technology-based learning media is increasing along with technological advances. Powtoon is one of the highly inventive web-based applications that allows educators to create dynamic and interactive visual presentations to increase student interest and understanding. However, there are still many educators who do not know that with the help of innovative and interactive learning media they can support learning objectives. The aim of community service activities is to provide training and assistance in creating multimedia learning media based on Powtoon to increase creativity in teachers. The hope is that all teachers can improve the quality of learning which is able to make students motivated and enthusiastic in every learning process. The target of this community service activity is MI Teacher Miftahul Ulum Sidowungu, Menganti - Gresik District. The method used goes through several stages, namely, problem identification, planning, data collection, data analysis, action and evaluation or reflection. From the results of the implementation of community service which began with socialization, the participants were very enthusiastic, as seen through question and answer activities related to the use of media and use of the Powtoon application. Products that have been created with the application of creativity assessment in using Powtoon received a percentage of 88%, teachers have been able to create media with Powton from simple ones to displaying videos. Apart from that, the response from Powtoon users was very positive, shown by the percentage result of 88%. This training and mentoring activity adds insight and increases teacher creativity in creating learning media so that students accept the material more easily, are more enthusiastic, and interactive media can help improve students' reasoning power.